Cortical excitability in patients with REM sleep behavior disorder with abnormal TRODAT-1 SPECT scan: an insight into prodromal Parkinson’s disease - Su, Siao-Chu; Chen, Rou-Shayn; Chen, Yi-Chieh; Weng, Yi-Hsin; Hung, June; Lin, Yi-Ying (Frontiers in Neurology, 2023)
Introduction: REM Sleep Behavior Disorder (RBD) has been highlighted to identify a patient with prodromal Parkinson's disease (PD). Although many studies focus on biomarkers to predict an RBD patient’s evolution from prodromal PD to clinical PD, the neurophysiological perturbation of cortical excitability has not yet been well elucidated. Moreover, no study describes the difference between RBD with and without abnormal TRODAT-1 SPECT. Methods: By measuring the amplitude of motor evoked potentials (MEP), the cortical excitability changes after transcranial magnetic stimulation (TMS) was evaluated in 14 patients with RBD and eight healthy controls (HC). Seven of the 14 patients with RBD showed abnormal TRODAT-1 (TRA-RBD), and seven normal (TRN-RBD). The tested parameters of cortical excitability include resting motor threshold (RMT), active motor threshold (AMT), short-interval intracortical inhibition (SICI), intracortical facilitation (ICF), contralateral silence period (CSP), and input-output recruitment curve. Results: The RMT and AMT showed no difference among the three studied groups. There was only SICI at inter-stimuli-interval 3 ms revealing group differences. The TRA-RBD demonstrated significant differences to HC in these aspects: decreased SICI, increased ICF, shortening of CSP, and augmented MEP amplitude at 100% RMT. Moreover, the TRA-RBD have smaller MEP facilitation ratio at 50% and 100% of maximal voluntary contraction when compared to TRN-RBD. The TRN-RBD did not present any difference to HC. Conclusion: We showed that TRA-RBD shared similar cortical excitability changes with the clinical PD. These findings would provide further insight into the concept that RBD is the highly prevalent entity in prodromal PD.